Feasibility Study on Additive Manufacturing of Feed Horn Operating in D-Band - Giuseppe Addamo; Lorenzo Scalcinati; Mario Zannoni; Oscar Antonio Peverini; Flaviana Calignano (Sensors)
This paper presents the outcomes of a feasibility study on the manufacturing of D-band horn antennas through the Low Power Bed Fusion process. Different prototypes have been realized and tested, showing nice results in terms of the co-polarization component. On the other hand, a spurious cross-polarization component is present in the radiation pattern even in the principal planes, limiting the device to single-polarization applications. A mechanical study of the realized devices has been conducted on the horn internal channel to understand the reasons for this issue, and, subsequently, to address where to improve the manufacturing process.